Quantitative goals for monetary policy - Antonio Fatás; Ilian Mihov; Andrew K. Rose (European Central Bank (ECB), 2006)
We study empirically the macroeconomic effects of an explicit de jure quantitative goal for monetary policy. Quantitative goals take three forms: exchange rates, money growth rates, and inflation targets. We analyze the effects on inflation of both having a quantitative target, and of hitting a declared target; we also consider effects on output volatility. Our empirical work uses an annual data set covering 42 countries between 1960 and 2000, and takes account of other determinants of inflation (such as fiscal policy, the business cycle, and openness to international trade), and the endogeneity of the monetary policy regime. We find that both having and hitting quantitative targets for monetary policy is systematically and robustly associated with lower inflation. The exact form of the monetary target matters somewhat (especially for the sustainability of the monetary regime), but is less important than having some quantitative target. Successfully achieving a quantitative monetary goal is also associated with less volatile output.
Keywords: E52; 330; business cycle; exchange; Growth; inflation; Money; rate; TARGET; transparency; Geldpolitik; Regelbindung versus Diskretion; Inflationssteuerung; Schätzung; Welt; Kleinste-Quadrate-Methode